ESENSI PENDIDIKAN AGAMA ISLAM DALAM MEWUJUDKAN KESEHATAN MENTAL SISWI MA AL-WASHOYA NGORO JOMBANG JAWA TIMUR - Mahdiyyah, Rasyidatun; Hosna, Rofiatul; Arini, Aida (EL-Islam, 2024)
Islamic religious education is at the same time faith education and charity education. And because Islamic teachings contain teachings about people's personal attitudes and behavior towards a prosperous life. In a historical-sociological context, Islamic education is defined as religious or Islamic education or teaching (al-tarbiyah al-diniyah, ta'lim al-din, al-ta'lim al-dini and al-ta'lim al-islami). in the context of tarbiyah al-Muslimin (educating Muslims), until completion. and differentiate it from secular education. The aim of Islamic religious education is to shape the nation's next generation into people who understand religion and can practice it well and correctly. Mental health is a state of well-being in individuals who realize their potential, are able to cope with the normal stresses of life, can work productively and fruitfully, and are able to make a contribution to their community. Mental health refers to how individuals are able to adapt and interact well. Mental health is always linearly related to human life span, therefore mental health is very important, especially for students who are focused on gaining knowledge, therefore the understanding and example of an educator is very necessary for students in maintaining and realizing mental health. The focus of this research includes: The essence of Islamic religious education in realizing mental health. This type of research uses case studies which aim to find out something comprehensively. This research includes field research by analyzing several things related to the nature of Islamic religious education in realizing mental health, by ensuring that children can apply the Islamic religious education learning they have received properly and correctly. Based on research, it was found that the results of the nature of Islamic religious education in realizing mental health: 1) Can be realized by learning Islamic religious education which is applied in everyday life 2) Religious activities are provided in schools and encouraged. through collaboration between the Principal, teachers and students in educating and developing children so that they run well, are active and conducive. So that it creates mental health in humans, the souls of female students and they are able to look after them well because they are equipped with this religion. 3) Female students understand how to realize and maintain good and correct mental health.